Replacing commercial concentrate by Ficus thonningii improved productivity of goats in Ethiopia - Balehegn, M.; Eik, L.O.; Tesfay, Y. (Springer, 2014)
Ficus thonningii (FT) is an important multipurpose fodder tree providing economic and ecological benefits across arid and semi-arid areas in Africa. Despite its availability in many Sub-Saharan African countries, there is lack of information on its effect on animal productivity. Twenty-four male weaned highland goats of age 7 ± 1.5 months were randomly assigned to four dietary treatments in a completely randomized block design. All animals were fed wheat straw, water, and salt licks ad libitum. The control group (T1) was fed concentrate mixture at 2 % of their body weight, while in T2, T3, and T4, 25, 50, and 75 % of the weight of concentrate (DM basis), respectively, was replaced by sun dried FT leaf meal. FT leaf meal had acceptable levels crude protein (CP), neutral detergent fiber (NDF), and tannins and has resulted in increased body weight in all treatments. Goats fed T3 diet showed significantly higher (P < 0.05) values in terms of feed intake, body weight gain, some carcass attributes, and local meat quality indicators than the rest of the treatments. An increase in proportion of FT leaf meal beyond 50 %, however, resulted in decreased body weight gain, and other carcass parameters, despite increased feed intake. Therefore, F. thonningii can be used to replace commercial concentrate mixture up to 50 % to improve feed intake and productivity of Ethiopian highland goats.